Copper-incorporated hierarchical wire-on-sheet α-Ni(OH)2 nanoarrays as robust trifunctional catalysts for synergistic hydrogen generation and urea oxidation. Issue 22 (21st May 2019) - Xie, Junfeng; Gao, Li; Cao, Shanshan; Liu, Weiwei; Lei, Fengcai; Hao, Pin; Xia, Xinyuan; Tang, Bo
Abstract : Copper-incorporated α-Ni(OH)2 nanoarrays with a unique hierarchical wire-on-sheet structure and local Ni 3+ species are explored as efficient trifunctional electrocatalysts for urea oxidation and water electrolysis. Abstract : Copper-incorporated α-Ni(OH)2 nanoarrays with a unique hierarchical wire-on-sheet structure and local Ni 3+ species are explored as efficient trifunctional electrocatalysts for urea oxidation and water electrolysis. The unique hierarchical morphology can not only provide abundant reactive sites for the in situ generation of catalytically active species for electrooxidation reactions, but also guarantee a robust and conductive skeleton for facile charge transport and offer effective buffering space for the volume change during the Ni 2+ -to-Ni 3+ pre-oxidation process. Besides, the presence of local Ni 3+ ions and the optimal Cu concentration further enhance the electrooxidation behaviors such as the UOR and OER, and the role of the Cu dopant in boosting the HER activity toward long-term operation is illustrated as the generation of low-valence Cu that could effectively facilitate the electron transfer process. As a result, remarkable UOR, HER and OER performance can be achieved with the synergistic benefits of large surface area, enhanced charge transfer and robust structural stability, which can be beneficial for electrolytic cells for efficient coupled urea electrolysis and overall water splitting.